Exploring the Impact of IRE Quality and Self-Control on Religious Tolerance in Junior High Students - Alfina Masruroh; Mustaqim Mustaqim; Nur Khoiri; Muhammad Azhar (AL-ISHLAH: Jurnal Pendidikan, 2025)
Intolerance remains a prevalent issue in Indonesian schools, necessitating an understanding of the factors influencing students’ religious tolerance. This study examines the impact of Islamic Religious Education (IRE) quality and self-control on students’ religious tolerance attitudes among junior high school students in Southern Kendal Regency. A quantitative survey approach was employed, with data collected from 267 students using proportional random sampling. Self-control and religious tolerance attitudes were assessed through questionnaires, while IRE quality was measured through structured classroom observations. Statistical analysis was conducted to determine the contribution of these variables to students’ tolerance levels. Findings indicate that both IRE quality and self-control significantly influence students’ religious tolerance attitudes. Statistical analysis reveals that IRE quality contributes 56.9%, while self-control accounts for 48.8% of students' tolerance attitudes. When analyzed simultaneously, the coefficient of determination shows a combined influence of 83.1%. These results underscore the importance of quality religious education and self-regulation in fostering a tolerant school environment. The study highlights the role of effective IRE instruction in shaping students' perspectives on tolerance. Additionally, the ability to exercise self-control enhances students’ capacity to navigate religious diversity with respect. To enhance religious tolerance, educators should integrate tolerance values into IRE curricula and incorporate self-control training through simulations or role-plays. Future research should explore additional socio-cultural factors influencing religious tolerance among students.